2007
DOI: 10.1111/j.1559-1816.2007.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics in Self‐Regulation: Plan Execution Self‐Efficacy and Mastery of Action Plans

Abstract: This study investigated whether an individual's plan execution self‐efficacy precedes mastery of the respective action plan or vice versa. Study participants were 122 cardiac rehabilitation patients. Plan execution self‐efficacy and mastery of a personal action plan on physical activity were assessed each week for 6 weeks after discharge from rehabilitation. Physical exercise was assessed 2 months after discharge. Multilevel cross‐lagged panel analyses resulted in a positive effect of mastery on subsequent sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…Exploring age associations with the key variables under study, the findings resembled those by Scholz et al. () and indicated that older persons reported higher planning at baseline. A longer lifetime and a more extensive accumulated history of initiating and adapting to changes are likely associated with a greater experience in planning in older individuals (Freund & Baltes, ; Reuter et al., ).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Exploring age associations with the key variables under study, the findings resembled those by Scholz et al. () and indicated that older persons reported higher planning at baseline. A longer lifetime and a more extensive accumulated history of initiating and adapting to changes are likely associated with a greater experience in planning in older individuals (Freund & Baltes, ; Reuter et al., ).…”
Section: Discussionsupporting
confidence: 72%
“…A study with individuals at increased risk of type‐two diabetes (Hankonen, Absetz, Ghisletta, Renner, & Uutela, ) also did not find any gender differences in baseline self‐efficacy nor in planning. Regarding associations with age, a planning intervention study with cardiac rehabilitation patients by Scholz, Sniehotta, Burkert, and Schwarzer () found that older patients showed significantly higher baseline planning levels compared to younger patients. A representative epidemiologic study with N = 8,152 German adults aged 18 to 79 years found that younger persons reported being more physically active than older individuals, whereas men reported higher physical activity than women (Krug et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Taking a within‐subject perspective, Scholz and colleagues (2007) show how initial mastery in implementing individual activity plans predicts increase in specific self‐efficacy which after two months turned out to be a good predictor of general physical activity. An alternative explanation of successful planning is that it reinforces the use of planning as a self‐regulatory strategy.…”
Section: Mediators Of Planning Over Timementioning
confidence: 99%
“…In terms of self‐efficacy, social‐cognitive theory postulates that the most important source of self‐efficacy is mastery experience (Bandura, 1997). As recent research shows, mastery experience (indicated by successful behavior change) seems to be triggered by planning, which in turn promotes higher self‐efficacy (Scholz et al., 2007). The fact that we did not find an effect of the experimental treatment on fat consumption (as an indicator of mastery experience) is not necessarily a contradiction to this interpretation, as we did not have a direct measure of mastery in this study.…”
Section: Discussionmentioning
confidence: 99%
“…According to the HAPA, volitional variables serve as mediators of planning interventions due to the volitional nature of the planning construct. More precisely, repeated planning interventions might affect self‐efficacy by enabling mastery experiences (e.g., Scholz, Sniehotta, Schüz, & Oeberst, 2007). Moreover, self‐reported action and coping planning as a self‐administered self‐regulatory strategy should be promoted by repeated planning interventions which thereby unfold their effects on behavior change (e.g., Luszczynska et al., 2007).…”
Section: Mediators Of Planning Effectivenessmentioning
confidence: 99%